2001
DOI: 10.1002/hup.287
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine (4 mg/kg) influences sustained attention and delayed free recall but not memory predictions

Abstract: This experiment was conducted to examine the influence of a moderate dose of caffeine (4 mg/kg) on delayed memory, metamemory, and sustained attention. One hundred and forty-two volunteers ingested either caffeine or placebo during a study session which included three different memory tasks (free recall, cued recall, and recognition), and they made predictions of future memory performance. On day 2, participants again ingested either caffeine or placebo and completed memory tests. Sustained attention performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Because the cognitive effects of caffeine can vary with time of day (Anderson and Revelle, 1994;Kelemen and Creeley, 2001), all testing was conducted at approximately the same time of day (the afternoon). Participants were also instructed to abstain from caffeine for 4 h prior to the experiment and to not eat or drink anything for 1 h before arriving.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Because the cognitive effects of caffeine can vary with time of day (Anderson and Revelle, 1994;Kelemen and Creeley, 2001), all testing was conducted at approximately the same time of day (the afternoon). Participants were also instructed to abstain from caffeine for 4 h prior to the experiment and to not eat or drink anything for 1 h before arriving.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…For example, the detection of a single digit is significantly impaired by increasing doses of alcohol (Rohrbaugh et al, 1988). Caffeine has also been found to increase the number of correct hits for both single and multiple digit versions of the task (Brice and Smith, 2001;Kelmen and Creeley, 2001). However, findings relating to caffeine-related improvements (speeding) in reaction time are less conclusive.…”
Section: Sustained Attentionmentioning
confidence: 97%
“…Caffeine Kelmen and Creeley (2001) 120 Between groups; Placebo versus caffeine (4 mg/kg) across two days (Caffeine-Caffeine, Caffeine-Placebo, PlaceboCaffeine, Placebo-Placebo).…”
Section: Sustained Attentionmentioning
confidence: 99%
“…Trial making is a complex task that requires sustained attention, alertness, speeded motor activity to be activated at the same time. Previous studies showed a positive effect of caffeine on sustained attention [36] alertness [25] and motor activity [43] separately. Trail making test confirms our hypothesis that a merging of facilitation events might produce a combinatory effect on cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies reported inconsistent results. These studies used different tasks [25,26], varied the dosage of caffeine and L-theanine in the tea [26][27][28], tested participants in different cognitive tasks [8,20,29,30]. Therefore, we aimed to identify the influence of BT consumption on human cognitive functioning, testing the participants in a wide range of cognitive tasks with a low dose that is 50 mg and 15 mg respectively.…”
Section: Aim Of the Studymentioning
confidence: 99%